2015
DOI: 10.3168/jds.2014-9061
|View full text |Cite
|
Sign up to set email alerts
|

Examination of weekly mammary parenchymal area by ultrasound, mammary mass, and composition in Holstein heifers reared on 1 of 3 diets from birth to 2 months of age

Abstract: Monitoring in vivo growth of mammary parenchyma (PAR) has historically been difficult, necessitating slaughter studies to measure PAR quantity. Advances in ultrasound (US) technology warrant revisiting its use as a noninvasive tool to monitor PAR growth in vivo. The level of nutrient intake during the first 2mo of life may affect measures of mammary growth and composition. Objectives were to examine the utility of US as an in vivo tool to quantify PAR cross-sectional area in Holstein heifers reared on 1 of 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 21 publications
(42 reference statements)
6
52
2
1
Order By: Relevance
“…A dual-energy x-ray absorptiometry (DXA) machine was available for use during this trial. Due to increased interest in gauging mammary gland development noninvasively (Esselburn et al, 2015), we used a Lunar Prodigy Advance DXA machine (PA+130744, GE Healthcare, Little Chalfont, UK) to assess mammary tissue composition differences after the animals were killed. Scanning of each udder half lasted approximately 4 min.…”
Section: Animal Handling and Experiments Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A dual-energy x-ray absorptiometry (DXA) machine was available for use during this trial. Due to increased interest in gauging mammary gland development noninvasively (Esselburn et al, 2015), we used a Lunar Prodigy Advance DXA machine (PA+130744, GE Healthcare, Little Chalfont, UK) to assess mammary tissue composition differences after the animals were killed. Scanning of each udder half lasted approximately 4 min.…”
Section: Animal Handling and Experiments Designmentioning
confidence: 99%
“…In their recent report, Esselburn et al (2015) describe some of the history of the use of udder measurements and palpation to evaluate mammary development in heifer calves and demonstrate the utility of ultrasound for evaluating udder and mammary development in young heifers. We took advantage of available DXA scanning equipment to determine if this tool could be used to evaluate udder development in these heifers.…”
Section: Noninvasive Mammary Gland Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary glands consist of 2 major types of tissues that serve different functions. As summarized by Esselburn et al (2015), these are (1) epithelial tissue and surrounding stromal elements, collectively called mammary parenchyma (PAR), and (2) stromal tissue that lies adjacent to PAR and does not contain epithelial structures, and instead mainly consists of connective tissue structures such as adipose. For this reason, mammary stroma is often referred to as mammary fat pad.…”
Section: Technical Notementioning
confidence: 99%
“…Understanding of growth dynamics of these mammary tissues as well as the influence of nutrition on mammary gland development has been the subject of study over the years (Sejrsen et al, 1983;Brown et al, 2005;Meyer et al, 2006). Esselburn et al (2015) recently showed that in heifers younger than 2 mo of age, obtaining weekly PAR measurements via ultrasound was an effective quantitative tool for measuring changes in PAR area in vivo. Although estimation of PAR composition via ultrasonography was not an experimental objective of Esselburn et al (2015), those authors noted that such estimation is feasible.…”
Section: Technical Notementioning
confidence: 99%